Tecnologie e dati spaziali per una moderna governance del territorio Strumenti a supporto per una riforma del catasto - MediaGEO, a cura della redazione (GEOmedia, 2013)
This article outlines the methods and activities of the sector mapping in support of the important process of renewal of the entire cadastral system. Describes the modern technologies and spatial data available today that can assist in setting up complex issues of reforming the system of quantities cadastral and, more generally, in the processes for the fight against tax evasion in real estate.